EL SEGURO DE CAUCIÓN PARA GARANTIZAR EL PERCIBO DE CANTIDADES ANTICIPADAS EN LA CONSTRUCCIÓN Y VENTA DE VIVIENDAS EN LA DISPOSICIÓN ADICIONAL PRIMERA DE LA LEY 38/1999, DE 5 DE NOVIEMBRE, DE ORDENACIÓN DE LA EDIFICACIÓN - Baldomero, Eugenia Fernández (European Scientific Journal, ESJ, 2015)
The surety insurance issued to guarantee the receipt of advance payments for the construction and sale of properties has certain peculiarities, since the insurer shall indemnify the purchasers of homes under construction those amounts that had been deposited into the special account, opened in any financial entity by the promoter, regardless of his having issued or not the individual surety insurance certificate in favor of the insured buyer. The kind of surety governed by the rule is thus configured as a quasi-autonomous guarantee in order to ensure the protection of purchasers of properties under construction, the most effective way.